NEGRITUDE OBLITERADA NOS POEMAS E NA OBRA DE CAROLINA MARIA DE JESUS | THE OBLITERATION OF NEGRITUDE IN THE POEMS AND WORKS OF CAROLINA DE JESUS - Fernandez, Raffaella Andréa (Estudos Linguísticos e Literários, 2018)
Resumo: Esse texto discute os mecanismos de obliteração da temática da negritude na publicação de Antologia pessoal (1996) de Carolina Maria de Jesus com foco em dois poemas fundamentais intitulados “Os feijoes” e “Negros”. A invisibilidade desses poemas expressa a força transgressora da palavra NEGRO, saída da pena emblemática de uma vivência afroscescentrada. A contra narrativas da escritora foram forjadas ao longo das edições, camuflando esses conteúdos, assim como sua literalidade particular. Aspectos fundamentais que redefinem na atulidade seus procesos de criação para além do testemundo proveniente do “quarto de despejo”. Abstract: The present article discusses the mechanisms of obliteration of the concept of negritude occurring in the publication of Personal Anthology (1996) by Carolina Maria de Jesus, with a focus on two fundamental poems, titled “Os feijoes” (The Beans) and "Negros" (Negroes). The invisibility of these poems expresses the transgressive force of the word NEGRO, derived from the emblematic pen of an Afro-centred existence. The counter-narratives of the writer were forged throughout the editions, by whitewashing these contents, as well as their peculiar literality. These aspects are fundamental for redefining, in the present times, her creative processes, beyond the testimony coming from the "dumping room". Keywords: Carolina Maria de Jesus; Poetry; Edition; Negritude.